Learning to Model the Grasp Space of an Underactuated Robot Gripper Using Variational Autoencoder. Issue 7 (2021) - Rolinat, Clément; Grossard, Mathieu; Aloui, Saifeddine; Godin, Christelle
Abstract: Grasp planning and most specifically the grasp space exploration is still an open issue in robotics. This article presents a data-driven oriented methodology to model the grasp space of a multi-fingered adaptive gripper for known objects. This method relies on a limited dataset of manually specified expert grasps, and uses variational autoencoder to learn grasp intrinsic features in a compact way from a computational point of view. The learnt model can then be used to generate new non-learnt gripper configurations to explore the grasp space.